2003
DOI: 10.2174/0929866033479031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chemotactic Peptide Analogs with a Photoaffinity Cross-Linker as New Probes for Analysis of Receptor-Ligand Interaction

Abstract: Formylpeptide receptors are well-characterized receptors which participate in host defense responses of neutrophils. We designed and synthesized chemotactic peptide analog with p-benzoylphenylalanine (Bpa) and biotin to probe structural and mechanistic aspects of peptide-receptor interaction. These peptides possess biological activities which were dependent upon spacer residue length of and Bpa position. The covalent photoaffinity label was detected by Streptavidine-blot, which was inhibited by the parent pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Early studies on the angiotensin II receptor (45) and recent work on chemotactic peptide analogues (46) and the integrin receptor (47) showed that biotin can be used as a reporting tag instead of radioactive isotopes. However, most of these studies were hampered by the low affinity of the ligand analogues due to incorporation of biotin as a reporter tag.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on the angiotensin II receptor (45) and recent work on chemotactic peptide analogues (46) and the integrin receptor (47) showed that biotin can be used as a reporting tag instead of radioactive isotopes. However, most of these studies were hampered by the low affinity of the ligand analogues due to incorporation of biotin as a reporter tag.…”
Section: Discussionmentioning
confidence: 99%